Dementia care : a handbook for long-term care certified nursing assistants - Rubertino, Frosini (HCPro, 2014)
"This handbook will help certified nursing assistants (CNA) understand and address the challenging care needs of residents with dementia at each stage of the disease's progression. CNAs will benefit from the how-to guidance that breaks down CMS' initiative, and learn how to provide efficient and effective care to residents"--Page 4 of cover.